The rise and decline of the UK's provincial stock markets, 1869-1929 - Gareth Campbell; Meeghan Rogers; John D. Turner (Queen's University Centre for Economic History (QUCEH), 2016)
The London Stock Exchange was the largest capital market in the world at the beginning of the twentieth century, but Britain also had numerous other stock markets based in provincial cities and towns. This paper provides the first in-depth quantitative assessment of these markets. We find that they were an important source of financing for regional companies up until circa 1900 and our evidence suggests that their post-1900 decline was largely due to the changing characteristics of publicly-listed firms. We also find that the provincial and London markets became increasingly integrated over time.
Keywords: G10; N23; N24; 330; capital market; provincial stock exchanges; integration; cross listing